Proceedings of the 2013 Workshop on Hot Topics in Middleboxes and Network Function Virtualization 2013
DOI: 10.1145/2535828.2535830
|View full text |Cite
|
Sign up to set email alerts
|

Are TCP extensions middlebox-proof?

Abstract: Besides the traditional routers and switches, middleboxes such as NATs, firewalls, IDS or proxies have a growing importance in many networks, notably in entreprise and wireless access networks. Many of these middleboxes modify the packets that they process. For this, they to implement (a subset of) protocols like TCP. Despite the deployment of these middleboxes, TCP continues to evolve on the endhosts and little is known about the interactions between TCP extensions and the middleboxes.In this paper, we experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 10 publications
0
46
0
Order By: Relevance
“…This paper was the main motivation for Multipath TCP incorporating various techniques to cope with middlebox interference. More specifically, Multipath TCP has been designed to cope with middleboxes that: The interactions between Multipath TCP and real deployed middleboxes are also analyzed in [HotMiddlebox13]; a particular scenario with the FTP Application Level Gateway running on a NAT is described.…”
Section: Multipath Tcp Proxiesmentioning
confidence: 99%
“…This paper was the main motivation for Multipath TCP incorporating various techniques to cope with middlebox interference. More specifically, Multipath TCP has been designed to cope with middleboxes that: The interactions between Multipath TCP and real deployed middleboxes are also analyzed in [HotMiddlebox13]; a particular scenario with the FTP Application Level Gateway running on a NAT is described.…”
Section: Multipath Tcp Proxiesmentioning
confidence: 99%
“…For instance, in the case of sequence number translation that is SACK-naïve, performance suffers in proportion to loss rate [24]. For ECN, performance suffers when false congestion signals are inadvertently marked, experiencing dramatic performance impact if a congestion codepoint is added, or a TCP-layer congestion echo is added [6].…”
Section: Application Performancementioning
confidence: 99%
“…Indeed, it has been shown that middleboxes have a negative impact on the TCP protocol (and its extensions) evolution [5], [6]. Middleboxes may modify, filter, or drop packets that do not conform to expected behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…Each new mechanism has to be certified as middlebox-proof [6], [7]. For those researchers, a summary of the potential middlebox network interferences would be a valuable asset as they could easily confront their new protocol with potential issues caused by middleboxes.…”
Section: Introductionmentioning
confidence: 99%